Da Jerry Masslo alla legge Minniti-Orlando. Le politiche dell’immigrazione in Italia - Federico Tulli (Il sogno della farfalla, 2018)
The article depicts and analyses data on the presence of migrants in Italy as well as Italian immigration policies through the study of all the different laws and decrees that have been implemented in Italy from the Seventies up to now. There emerges that, until the end of the Eighties, Italians’ behaviour towards the presence of 500,000 migrants who resided in Italy was characterized by a sort of indifference. The great change happened at the beginning of the Nineties. As highlighted by data from ISTAT and the Home Office, the phenomenon of migration has become increasingly more evident, thereby drawing the attention of legislators and leading to the implementation of more frequent and complex rules to regulate migrants’ flow and presence over the territory. Today, there are more than 5 million migrants in Italy.